Pengaruh Pengetahuan Perpajakan, Kesadaran Wajib Pajak, dan Keadilan Pajak Terhadap Kepatuhan Wajib Pajak UMKM yang Terdaftar di KPP Pratama Balikpapan Timur - Diza Shianti; Yudea; Dika Karlinda Sari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the influence of tax knowledge, taxpayer awareness, and tax fairness on the compliance of MSME taxpayers registered at KPP Pratama Balikpapan Timur. The number of samples used in this study uses the accidental sampling technique. The analysis method used is the Partial Least Square-Structure Equation Model (PLS-SEM). The result of this study show that tax knowledge, taxpayer awareness, and tax fairness have an effect on the compliance of MSME taxpayers.